MIP-1α and MCP-1 as salivary biomarkers in periodontal disease - K.J. Nisha; Aparnna Suresh; A. Anilkumar; Shyam Padmanabhan (Elsevier, 2018)
Absract: Aim: Chemokines released by different host cells when exposed to the components of periodontopathic bacteria induce and maintain an inflammatory response in the periodontium. The aim of the study was to estimate the salivary levels of two chemokines, macrophage inflammatory protein-1 alpha (MIP-1α) and monocyte chemo attractant protein-1 (MCP-1) in health, gingivitis and periodontitis and to evaluate their role as reliable salivary biomarkers in discriminating gingivitis and periodontitis from health. Methods: A cross sectional study was designed to estimate the levels of MIP-1α and MCP-1 in whole unstimulated saliva from 75 patients who were divided into healthy (Group 1, n = 25), gingivitis (Group 2, n = 25) and chronic generalized periodontitis (Group 3, n = 25). MIP-1α and MCP-1 levels were estimated by using ELISA and were correlated with clinical parameters. ROC curve analysis was done to determine the sensitivity and specificity of these biomarkers in distinguishing periodontal disease from health. Results: Both the biomarkers were detected in all the saliva samples. There was a statistically significant difference in the concentration of both the analytes in Group 3 and Group 2 compared with Group 1 (p < 0.001). ROC curve analysis showed 100% sensitivity and specificity for MIP-1α and MCP-1 in discriminating periodontitis from health. For discriminating gingivitis from health, MIP-1α had a higher sensitivity and specificity (100% & 88% respectively) compared to MCP-1(84.1% & 80% respectively). Conclusion: There is a substantial increase in the concentration of both MIP-1α and MCP-1 with increasing severity of periodontal disease. Both the analytes showed promising results as biomarkers for discriminating periodontal disease from health. Keywords: Chemokines, Periodontal diseases, Saliva, Macrophage inflammatory protein-1, Monocyte chemoattractant protein-1